Aspectos epidemiológicos e fisiológicos da interação Colletotrichum gloeosporioides PENZ x mudas micropropagadas de cafeeiro (Coffea arabica) - Martins, Fernanda Gonçalves (2008)
This work was accomplished with the objective of studying the aspects of the infection of Colletotrichum gloeosporioides - isolated from stem and die back of coffee plants and leaves of mango; to study the development of symptoms of the pathossystem buttery x coffee plants through the evaluation of the incidence and severity of the disease; to observe the character of susceptibility between MOSPCSMM and MOSPSSMM; to confirm the relationship between C. gloeosporioides and die back in plants obtained by tissue culture and to observe in different times, to determine the isolated effects of C. gloeosporioides on the of pigments´ contents (chlorophyll the, b and total), total soluble phenols and soluble lignin in seedlings of coffee obtained by tissue culture and artificially inoculated. The experiments were carried out in DIC and in DBC. The plants were inoculated with a suspension of 2 x 106 conidia.ml-1 on the foliate area. The percentage of germination conidial and apressoria formation were evaluated at 6, 12, 18, 24, and 48 hours after the inoculation. The evaluations of the incidence and severity were accomplished at 5 days intervals, it of beginning 7 days after the inoculation with duration of 30 days. AT 3 and 7 days after inoculation were quantified contents of pigments of phenols and lignin. The spores´ germination occurred between 6 and 12 hours after the inoculation when some conidia emitted one or two germ tubes. We verified that there was significant difference to 1% of significance for the Scott-Knott test between isolated studied in this work. Besides, it showed that there was difference in the germination between isolated of MOSPSSMM. In additional there was not significant difference between isolated of MOSPCSMM studied, they presented similar effects on the medium germination of conidia. The apressoria formation was observed 6 hours after inoculation. MOSPSSMM and MOSPCSMM showed resistant to the isolated I, susceptible and moderately susceptible to isolated II. MOSPCSMM were susceptible to isolated III, while MOSPSSMM were moderately susceptible. The first necrosis symptoms in the leaves seedlings from MOSPCSMM and MOSPSSMM were only observed at seventh day after inoculation. The pathogens´ presence reduced the contents chlorophyll significantly, in the times and in the two genetic materials studied. At 7 days after inoculation of healthy and diseased plants of coffee we observed larger contents of total soluble phenols and soluble lignin in response to the attack of C. gloeosporioides.